Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm00191
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces

Abstract: Strep.to.my'ces. Gr. adj. streptos pliant, bent; Gr. masc. n. mukês fungus; N.L. masc. n. Streptomyces pliant or bent fungus. Actinobacteria / Actinobacteria / Streptomycetales / Streptomycetaceae / Streptomyces Aerobic, Gram‐stain‐positive, non‐acid‐fast bacteria that form extensively branched substrate and aerial mycelia . Chemoorganotrophic, having an oxidative type of metabolism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 471 publications
3
7
0
Order By: Relevance
“…The whole-genome sequencing showed that the genome of strain P38-E01 T consists of 6,158,643 bp assembled in 10 scaffolds with an average coverage of 364-fold. The DNA %G + C content was 71.4%, which is in concordance with the genus characteristics ( Kämpfer, 2015 ). Further genomic information on strain P38-E01 T is listed in Table 3 .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The whole-genome sequencing showed that the genome of strain P38-E01 T consists of 6,158,643 bp assembled in 10 scaffolds with an average coverage of 364-fold. The DNA %G + C content was 71.4%, which is in concordance with the genus characteristics ( Kämpfer, 2015 ). Further genomic information on strain P38-E01 T is listed in Table 3 .…”
Section: Resultssupporting
confidence: 78%
“…The cell wall peptidoglycan contains LL-diaminopimelic acid. All described chemotaxonomic characteristics are typical for the genus Streptomyces ( Kämpfer, 2015 ) and confirmed that the analyzed strain does belongs to this genus.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…At the taxonomic level, the genus Streptomyces forms part of the Bacteria superkingdom, the Actinomycetota phylum, the Actinomycetia class, the Streptomycetales order, and the Streptomycetaceae family [ 5 , 6 ]. These microorganisms are characterized as filamentous multicellular bacteria that are Gram-positive, facultatively aerobic, mesophilic, neutrophilic, and chemoorganotrophic, with an oxidative metabolism [ 7 ]. Concerning their life cycle, these bacteria develop a vegetative mycelium and an aerial mycelium that forms chains of immobile reproductive spores [ 7 , 8 ].…”
Section: Streptomyces the Biotech Gold Minementioning
confidence: 99%
“…Petri plates were incubated at 28 °C from 7 to 14 days. The emerging actinobacterial type colonies with different morphological characteristics (Kämpfer, 2015) were selected. Spores and/or mycelia of the isolated actinobacteria were preserved with 25% glycerol at -80 °C (Shepherd et al, 2010).…”
Section: Actinobacteria Isolationmentioning
confidence: 99%